The Role of Law Enforcement in Community-Based Drug Treatment and its Impact on Crime Prevention - Poothakool, Krisanaphong (2018)
In line with trends in other countries the Royal Thai Police acknowledges the need for more community-oriented approaches which are responsive to local contexts. However, the development of such approaches to policing needs also to engage with responses to illicit drug use locally, which would include a wider definition of harm reduction and accommodate the work of public health partners their initiatives, such as needle-exchange.The present study examines the role of law enforcement officers in community-based drug treatment in the Chiang Mai region of the Upper North, through use of in-depth, qualitative interviews with key stakeholders, which included senior police, judges, public health managers, NGO workers and local community leaders.Most interviewees expressed concern that not enough was being done to address drug use in local communities, and barriers to police adopting a harm reduction approach locally included government-directed arrest quotas and lack of experience in working co-operatively with public health partners. Effective police involvement required coordinated policy-change and officer training to develop understanding and ways of working to support community-based drug treatment